The Ability of Vaping Technology to Deliver an Equivalent Respirable Dose of Beclomethasone Dipropionate Compared to Nebulization - Cyrille Bruneau; Clément Mercier; Lara Leclerc; Jérémie Pourchez (Pharmaceutics)
Background/Objectives: This study focuses on the ability of vaping technology to deliver beclomethasone dipropionate compared to nebulization. Methods: An in vitro comparison of aerosol properties in terms of respirable dose with the Glass Twin Impinger and the mass median aerodynamic diameter using the Next Generation Impactor was performed. The respirable dose delivered in a vaping drug delivery system (VDDS) puff as a function of concentration was quantified by high-pressure liquid chromatography coupled with an ultraviolet detector. Results: The mass of drug contained in a single puff of 55 mL of aerosol varied between 0.94 and 1.95 µg for a refill liquid concentration range of 400 to 1600 µg/mL. The analysis of the particle size distribution shows an advantage for a VDDS in producing smaller particles compared to nebulization (1.56 ± 0.05 µm vs. 2.30 ± 0.19 µm). In total, 81 puffs are needed to reach the dose equivalent to nebulized beclomethasone dipropionate under these specific experimental conditions, which corresponds to an aerosol duration of about 4 min (i.e., four times lower than the jet nebulizer) and a patient administration time of about 45 min (i.e., three times higher than the jet nebulizer). Conclusions: The results show the potential of vaping devices as an alternative to nebulizers for the administration of beclomethasone dipropionate in an equivalent respirable dose.